2021
DOI: 10.3390/molecules26144155
|View full text |Cite
|
Sign up to set email alerts
|

Spin Crossover in Nickel(II) Tetraphenylporphyrinate via Forced Axial Coordination at the Air/Water Interface

Abstract: Coordination-induced spin crossover (CISCO) in nickel(II) porphyrinates is an intriguing phenomenon that is interesting from both fundamental and practical standpoints. However, in most cases, realization of this effect requires extensive synthetic protocols or extreme concentrations of extra-ligands. Herein we show that CISCO effect can be prompted for the commonly available nickel(II) tetraphenylporphyrinate, NiTPP, upon deposition of this complex at the air/water interface together with a ruthenium(II) phth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This substrate titration experiment at 120 K, therefore suggests that the 5‐coordinate [Co( 1 )( 3 ) n =1 ] species appears most abundant and this can exhibit a distribution between LS and HS states, whereas the [Co( 1 )] and 6‐coordinated adducts do not. It should also be noted that a temperature dependent equilibrium between the different coordination numbers 4, 5 and 6 ( n =0–2), likely exists and can inevitably alter the degree of coordination and spin state of the cobalt center, as indeed demonstrated in Ni(II) Schiff base complexes [47–49] . For example, Thies et al [47] .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This substrate titration experiment at 120 K, therefore suggests that the 5‐coordinate [Co( 1 )( 3 ) n =1 ] species appears most abundant and this can exhibit a distribution between LS and HS states, whereas the [Co( 1 )] and 6‐coordinated adducts do not. It should also be noted that a temperature dependent equilibrium between the different coordination numbers 4, 5 and 6 ( n =0–2), likely exists and can inevitably alter the degree of coordination and spin state of the cobalt center, as indeed demonstrated in Ni(II) Schiff base complexes [47–49] . For example, Thies et al [47] .…”
Section: Resultsmentioning
confidence: 96%
“…It should also be noted that a temperature dependent equilibrium between the different coordination numbers 4, 5 and 6 (n = 0-2), likely exists and can inevitably alter the degree of coordination and spin state of the cobalt center, as indeed demonstrated in Ni(II) Schiff base complexes. [47][48][49] For example, Thies et al [47] showed that within the temperature range 298-328 K, the association constants for binding a single pyridyl ligand to a Ni(II)-porphyrin forming a 5-coordinate complex and a second pyridyl ligand forming a 6-coordinated complex decreases as the temperature increases. As such, at lower temperatures, more substrate binding is expected, and this in turn will alter the amount of the HS versus the LS states, as revealed by the different EPR signals for the two states.…”
Section: Cw Epr Of [Co(1)(x)] (X = 2-6) Adducts Under Anaerobic Condi...mentioning
confidence: 99%
“…Finally, it is worth mentioning the existence of the coordination-induced spin state switch (CISSS). [86][87][88][89][90][91][92][93][94][95] This phenomenon is defined as a switch in the spin state of the metal centre, due to a change of the coordination number of the central ion. In most cases, the switch in the spin state is achieved by light irradiation (ligand-driven coordinationinduced spin state switching, LD-CISSS) 87,88,90,[94][95][96][97] or takes place in solution [86][87][88][89]91,92,[94][95][96][97][98][99][100][101] or in thin films/monolayers.…”
Section: Jose Sanchez Costamentioning
confidence: 99%
“…Nevertheless, while the effect of pressure on the processes of redox isomerization is mentioned in the literature for bulk samples [16][17][18], for surface/interfacial systems this issue remains poorly investigated. Meanwhile, the intrinsically asymmetric nature of air/water and air/solid interfaces often enables processes which can be almost impossible in bulk media [19,20].…”
Section: Introductionmentioning
confidence: 99%